(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the use of didactic game technologies to increase students’ strong motivation to learn is the main idea of some pedagogical technologies and is analyzed as a factor ensuring their effectiveness.